A CRITICAL ANALYSIS INTO THE EMERGENCE OF AUTHENTIC LEADERSHIP AND ITS IMPLICATIONS UPON ORGANIZATIONS - Rao Mangipudi, Mruthyanjaya; Prasad, KDV (The journal of contemporary issues in business and government, 2022)
Leadership entails creating an environment in which people feel safe and empowered enough to express unpopular opinions without fear of repercussions. The purpose of this paper is to explore about authentic leadership, its meaning, the process of becoming authentic, the impact of authenticity, the circumstances where the leaders not be too authentic, and why certain habits are not necessary for good leadership. The author considered heavily secondary data in formulization of the philosophy including certain surveys, reports, interviews conducted by prominent entities, and his personal past work experiences in terms of case study, adjoining the Indian Hindu mythology, too to provide a better perspective that revolves around authenticity and its significance. Despite the fact that authenticity fosters healthier and stronger connections with customers, people, investors, vendors, and other ecosystem stakeholders, the participants identified specific personality characteristics (such as sarcasm or anger) as the leading causes of workplace unhappiness. It is not worth devoting energy to continually self-monitoring one's (leader’s) own behaviour in order to ensure that it is under control. When someone attempts to be completely authentic, there is a dark side. Authentic leadership can sometimes be awful leadership. The paper maintains that authentic leadership is all about enabling and empowering the people around. Before being authentic, it is pertinent to think of the motivations for disclosures; whether the leader has authority to talk about the subject matter; whether the leader is meaningful by sharing such facts.